Effectiveness of create sensitivity model on glycemic control and quality of life among patients with type 2 diabetes - Dini Rudini; Yulia Indah Permata Sari; Putri Irwanti Sari; Yosi Oktarina (JKP (Jurnal Keperawatan Padjajaran))
Background: Type 2 diabetes significantly affects patients' quality of life (QOL). The "Create Sensitivity" model, integrating cognitive restructuring, patient discharge planning, self-care, and hope cultivation, offers a holistic approach to address these patients' psychological and emotional challenges.